1997
DOI: 10.1070/rc1997v066n04abeh000291
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene hydrides: synthesis, properties, and structure

Abstract: The results of studies on the methods of synthesis of exohedral fullerene hydrides, including the reduction of fullerenes by hydrocarbons, the catalytic hydrogenation of fullerenes, etc., are surveyed. Much attention is devoted to the state of hydrogen in solid fullerene hydrides, the structure of fullerene hydrides, and their reactivity. The bibliography includes 148 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 110 publications
1
35
0
Order By: Relevance
“…Fullerenes including [60]fullerene are strained alkenes with high degree of electrophilicity, which in combination with 60 propensity to various types of coordination, possibility of changing coordination depending on metal oxidation state, ability to accept electrons and/or hydrogen atoms in the reactions with donors [150] allowed one to expect the participation of fullerene ligand in multiple hydrogen transfer in one act of -activation by metal complex. Fullerides of platinum metals, 60 (M = Pt, Pd [151,152]) were studied as components of systems activating -bonds (Fig.…”
Section: Fig 22 Herementioning
confidence: 99%
“…Fullerenes including [60]fullerene are strained alkenes with high degree of electrophilicity, which in combination with 60 propensity to various types of coordination, possibility of changing coordination depending on metal oxidation state, ability to accept electrons and/or hydrogen atoms in the reactions with donors [150] allowed one to expect the participation of fullerene ligand in multiple hydrogen transfer in one act of -activation by metal complex. Fullerides of platinum metals, 60 (M = Pt, Pd [151,152]) were studied as components of systems activating -bonds (Fig.…”
Section: Fig 22 Herementioning
confidence: 99%
“…Hydrogenation of fullerite C 60 is normally realized at T = 450-850 K and P = 1 MPa -2 GPa in presence of catalyzers (Goldshleger and Moravskii 1997;Tarasov et al 2001). Under these conditions kinetic limitations become less important and the significance of thermodynamic control increases.…”
Section: Equilibria Of Reactions Of C 60 H 2n Hydridesmentioning
confidence: 99%
“…It was found that in the synthesis the mixtures of the hydrides with n = 1, 2, 3, 4, 18, 21-24 are formed (Goldshleger and Moravskii 1997). Perhydrofullerane C 60 H 60 has not been experimentally obtained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations